1982
DOI: 10.1111/j.1365-2761.1982.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication of infectious pancreatic necrosis virus in trout leucocytes and detection of the carrier state

Abstract: The exact cellular site of replication of infectious pancreatic necrosis virus (IPNV) in carrier fish is unknown. In order to determine if IPNV replicates in trout leucocytes, we purified leucocytes from normal (non-carrier) trout and separated the cells into an adherent and a non-adherent population. IPNV replicated in less than 0-01 % of the adherent leucocytes with a yield of about 400 p.f.u./cell. IPNV also became associated with less than 0-07% of the non-adherent leucocytes; either IPNV did not replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 10 publications
6
23
1
Order By: Relevance
“…In general, negligible levels of virus and few virus-positive fish were detected in assays of plasma from spawning and post-spawning fish. Our results with the plasma fraction corresponded with the results of Yu et al (1982) and Swanson & Gillespie (1982) who also found that, at best, virus was found infrequently in plasma in both naturally and experimentally infected fish. The results from white cell blood fractions were highly variable compared to those from sex products and tissues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, negligible levels of virus and few virus-positive fish were detected in assays of plasma from spawning and post-spawning fish. Our results with the plasma fraction corresponded with the results of Yu et al (1982) and Swanson & Gillespie (1982) who also found that, at best, virus was found infrequently in plasma in both naturally and experimentally infected fish. The results from white cell blood fractions were highly variable compared to those from sex products and tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Wolf et al (1963) were the first to demonstrate that IPNV could be detected in ovarian fluid, and McAllister et al (1987) showed that the cell and particulate components of ovarian fluid were particularly useful for detection of IPNV in asymptomatic fish. Swanson & Gillespie (1982) and Yu et al (1982) suggested that blood and blood fractions can be used for detection of IPNV in carrier and in experimentally infected fish, and Agius et al (1982Agius et al ( , 1983 and Hedrick et al (1986) evaluated different methods for processing tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytes may also serve as host cells for different viruses. IPNV infection and replication in leukocytes from salmonids has been reported (Yu et al 1982, Knott & Munro 1986, Johansen & Sommer 1995b. We have previously reported that cultures of head kidney macrophages isolated from Atlantic salmon show reduced ability to produce intracellular O 2 -after infection by IPNV in vitro (Johansen & Sommer 1995a).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of IPNV by co-cultivation of leuko cytes with a susceptible cell line has been reported by several authors (Swanson and Gillespie, 1982;Yu et al, 1982;Ahne and Thomson, 1986). Agius et al (1982) also described co-cultivation assays of head kidney cells isolated from IPNV survivors, on RTG-2 cell line, as a sensitive method to detect carriers.…”
Section: Detection Of Ipnv By Rt-pcr and Nested Pcrmentioning
confidence: 93%